How physical multimorbidity affected the mental health and healthcare utilization of patients with severe mental illness during the COVID-19 pandemic and earthquakes - Levaj, Sarah; Šimunović Filipčić, Ivona; Medved, Sara; Shields-Zeeman, Laura; Bolinski, Felix; Mikulić, Filip Luka; Rojnić Kuzman, Martina (Frontiers in Psychiatry, 2025)
BackgroundPeople with severe mental illness (SMI) commonly have chronic physical illnesses (CPI) and multimorbidity (CPM). The study aimed to investigate the association between mental health, healthcare utilization, and physical comorbidities in SMI patients affected by the double disasters in Croatia (two earthquakes and the COVID-19 pandemic), and identify predictors of CPI and CPM in this population.MethodA prospective study was conducted among 90 SMI patients at two-time points: May/June, 2020 (first COVID-19 wave and earthquake) and December, 2020/January, 2021 (second COVID-19 wave and earthquake).ResultsAt the first study point, the CPM group showed significantly higher severity of insomnia (p=.003; mean ISI scores (SD): 5.60(4.360), 9.47(6.802), and 10.83(8.026) for no-comorbidity group, CPI and CPM respectively), while CPI group showed higher perceived stress levels (p=.026; mean PSS scores (SD): 18.21(6.882), 22.32(4.619) and 21.67(3.343) for no-comorbidity group, CPI and CPM respectively) compared to the no-comorbidity group. CPI (5/18) and CPM (10/23) groups visited other specialized non-mental health care services significantly more frequently than those without comorbidity (7/46) (χ2 = 6.557, p=.038). A lower score of perceived social support by friends predicted CPI (OR=0.549; 95% CI:0.349-0.864; p=.010, corrected p=.04), but a higher score on alexithymia subscale “difficulty identifying feelings” predicted CPM (OR=1.235; 95% CI:1.071-1.424; p=.002, corrected p=.004).ConclusionPeople with SMI and CPI are especially vulnerable during the COVID-19 pandemic and disasters, as it affects their mental and physical health, leading to increased healthcare utilization. An integrated approach to treating SMI and CPI is necessary for the emergency health response.